2009
DOI: 10.1016/j.jbiomech.2009.04.043
|View full text |Cite
|
Sign up to set email alerts
|

A 3D finite element model of anterior vaginal wall support to evaluate mechanisms underlying cystocele formation

Abstract: Objectives-To develop a 3D computer model of the anterior vaginal wall and its supports, validate that model, and then use it to determine the combinations of muscle and connective tissue impairments that result in cystocele formation, as observed on dynamic magnetic resonance imaging (MRI).Methods-A subject-specific 3D model of the anterior vaginal wall and its supports was developed based on MRI geometry from a healthy nulliparous woman. It included simplified representations of the anterior vaginal wall, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 24 publications
8
88
0
2
Order By: Relevance
“…The results showed that if the pubovisceral impairment reached at a certain level, the anterior vaginal wall would prolapse; at 60% pubovisceral muscle impairment, a 90% impairment of apical support caused the prolapse to increase from 0.3 to 1.9 cm. In 2009, a three-dimensional (3D) finite element model of the anterior vaginal wall and its support system were developed by Chen et al [8]. Effects of the apical impairment and/or levator ani muscle impairment on prolapse size were evaluated.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that if the pubovisceral impairment reached at a certain level, the anterior vaginal wall would prolapse; at 60% pubovisceral muscle impairment, a 90% impairment of apical support caused the prolapse to increase from 0.3 to 1.9 cm. In 2009, a three-dimensional (3D) finite element model of the anterior vaginal wall and its support system were developed by Chen et al [8]. Effects of the apical impairment and/or levator ani muscle impairment on prolapse size were evaluated.…”
mentioning
confidence: 99%
“…The anterior vaginal wall was usually modeled as a separated part from the posterior compartment, which was entirely made up of the posterior vaginal wall and rectum. In addition, the ligaments were simulated by passive elastic springs [7] or 3D truss elements [8]. The oversimplification made it impossible to evaluate the shear stress in the lateral vaginal walls, which is, however, eagerly needed clinically.…”
mentioning
confidence: 99%
See 3 more Smart Citations